Perilaku Harian Tarsius (Tarsius spectrumgurskyae) Di Sekitar Sarang: Studi Kasus Di Hungayono Dalam Kawasan Taman Nasional Bogani Nani Wartabone - Zakaria, Zuliyanto; Delviyanti Lihawa, Sri; Utina, Ramli; Solang, Margaretha; Wahyuni K. Baderan, Dewi; Tri Nugroho, Bagus (Universitas Cokroaminoto Palopo, 2024)
The purpose of this study is to ascertain T. spectrumgurskyae's daily activities in the vicinity of nests in the Bogani Nani Wartabone National Park. Ad libitum sampling, also known as direct observation, involves observing behavior and documenting all actions during the observation period using activity limitations (ethogram table). A week of data collecting was conducted from May 5–11, 2024, from 5:00–17:00. The study's findings showed that 56.4% of tarsiers' behavior near the nest was resting, whereas 23.1% was avoidance, 12.2% was self-cleaning, 8.0% was shade-seeking, and less than 1% was playing or eating. The findings demonstrated that resting and avoidance behavior dominated tarsier activity in the vicinity of the nest during observation.